The Effect of Date Fruit (Phoenix dactylifera L.) Consumption on Autonomic Nerve Function and Hot Flash Manifestations in Menopausal Women - Winda Maulinasari Nasution; Siti Maryam Hasibuan; Lanny Apriani (JURNAL BIOSAINS, 2026)
Menopause is a natural phase in a woman’s life marked by decreased estrogen levels and symptoms such as hot flashes, which are linked to autonomic nervous system dysfunction. Hot flashes cause sudden heat sensations, sweating, flushing, and palpitations that can disrupt daily life. Date fruit is rich in antioxidants and phytoestrogens, making it a potential non-hormonal alternative to alleviate menopausal symptoms. This study aimed to analyze the effect of date fruit consumption on autonomic nerve function and hot flash manifestations in menopausal women. A quasi-experimental pretest–posttest control group design was used, involving menopausal women aged 45–60 years experiencing hot flashes at Midwife Hj. Dewi Sesmera’s Clinic, Medan City, North Sumatra. Participants were selected using purposive sampling. The intervention group consumed 50 grams of date fruit daily for eight weeks. Data were collected through questionnaires, interviews, and documentation. Autonomic nerve function was measured using the COMPASS-31 (Composite Autonomic Symptom Score-31), and hot flash frequency and intensity were assessed with the Menopause Rating Scale (MRS). Statistical analysis employed a paired t-test (p < 0.05) using SPSS version 24. Results showed that while improvement in autonomic nerve function was not statistically significant, the frequency and intensity of hot flashes significantly decreased in the intervention group.